PENGARUH VARIASI POTENSIAL ANODISASI TERHADAP SIFAT OPTIK TIO2 NANOTUBE ARRAYS (TNAS) MENGGUNAKAN METODE ANODISASI DUA TAHAP - Zahara; Sherly Kasuma Warda Ningsih (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Advances in science and technology have increased interest in semiconductor materials at the nanoscale, especially titanium dioxide (TiO2) with its characteristic optical properties such as band gap energy and light absorption. The growth of nanotube structures using an anodization method with parameters, namely pH, temperature, electrolyte composition, anodization potential, and time. The anodization potential has a significant influence on nanotube growth, including thickness and pore diameter. However, the higher the potential, the risk of charge recombination can occur. TNAs were prepared using a two-stage anodization method using potential variations of 40 V, 45 V, and 50 V for 1 hour in the first stage and 30 minutes in the second stage. UV-Vis DRS characterization showed that the potential of 40 V (3.22 eV), potential of 45 V (3.32 eV), and potential of 50 V (3.37 eV). The optimum potential is 40 V responsive to UV light.